Comparison of the effect of sambiloto (AS 201-01) tablet and dihydroartemisinin-piperaquine on macrophage MIF expression in mice placenta infected with Plasmodium berghei - Desak Ketut Ayu Aryani; Budi Prasetyo; Aty Widyawaruyanti; Widjiati Widjiati (Universitas Airlangga, 2018)
Objective: To compare the administration of sambiloto tablets (AS201-01) and dihydroartemisinin-piperaquine phosphate tablets in pregnant mice infected by P. berghei on the expression of MIF in the placenta.Materials and Methods: Experimental laboratory research, 24 pregnant mice were divided into 4 groups with randomization, ie. non-infected, placebo, sambiloto (AS201-01) and DHP groups. On day 9 P. berghei was infected, on day 11 the treatment was given, day 15 the surgery was performed, placental samples were taken, immunohistochemical staining was given, and MIF expression was assessed.Results: The expression of MIF in the group not infected with P. berghei had the lowest mean, while the highest mean was found in the placebo group. Uninfected groups were not significantly different from sambiloto (AS201-01) tablet group. Sambiloto tablet group (AS201-01) had lower MIF expression than DHP group, but it was not significantly different. Sambiloto tablet group (AS201-01) showed lower MIF expression than placebo. MIF expression in DHP group was lower than that in placebo group. From the lowest, the MIF expressions were as follows: group not infected with P. berghei, group receiving sambiloto (AS201-01) tablet, DHP group and placebo group.Conclusion: MIF expression in the placenta of pregnant mice infected with P. berghei and receiving sambiloto (AS20-01) tablets was not different from those receiving DHP tablets.